2017
DOI: 10.1111/asap.12146
|View full text |Cite
|
Sign up to set email alerts
|

Bad Apples? Attributions for Police Treatment of African Americans

Abstract: Numerous recent encounters between police officers and Black citizens have resulted in the deaths of African American men and have drawn renewed public scrutiny of police practices. We examine the public's attributions about these encounters. Does the public perceive violent confrontations between police officers and Black citizens as a result of broader problems in police practices or simply as isolated incidents? We employ attribution theory and social identity theory to understand how social and political i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Many Americans mistakenly attribute police brutality to a “few bad apples.” As policing researchers, legal scholars and activists have rightfully argued (e.g. Alexander, 2010; Dukes and Kahn, 2017; Haider-Markel and Joslyn, 2017; Harmon, 2012; Tyler et al , 2015), the issue is not the fruit but the tree itself (for review, see Hall et al , 2016). Law enforcement agencies were not established to protect and serve Black citizens; rather, the first police forces were created to preserve the institution of slavery and protect white assets by apprehending runaways and preventing revolts among enslaved people (Waxman, 2017).…”
Section: Second Racism Against Black People Includes – But Extends Well Beyond – Police Brutalitymentioning
confidence: 99%
“…Many Americans mistakenly attribute police brutality to a “few bad apples.” As policing researchers, legal scholars and activists have rightfully argued (e.g. Alexander, 2010; Dukes and Kahn, 2017; Haider-Markel and Joslyn, 2017; Harmon, 2012; Tyler et al , 2015), the issue is not the fruit but the tree itself (for review, see Hall et al , 2016). Law enforcement agencies were not established to protect and serve Black citizens; rather, the first police forces were created to preserve the institution of slavery and protect white assets by apprehending runaways and preventing revolts among enslaved people (Waxman, 2017).…”
Section: Second Racism Against Black People Includes – But Extends Well Beyond – Police Brutalitymentioning
confidence: 99%
“…We theorize that racial disparities in police killings are driven by a combination of macro‐level criminal policies and meso‐level organizational factors, not by micro‐level racism. In a recent study, Epp, Maynard‐Mooney, and Haider‐Markel () found that African American motorists were disproportionately stopped for “investigatory stops” by police officers of all races (cf. Antonovics and Knight ).…”
Section: Theoretical Perspective and Expectationsmentioning
confidence: 99%
“…The widespread belief of racialized policing in general-and racialized police killing in particular-has had a deleterious effect on levels of trust between minority citizens and law enforcement officers (Brunson and Gau 2015). dominant explanation for disproportionate police violence and police bias in general is what has been called the "rotten apple" theory of police misconduct (Haider-Markel and Joslyn 2017;Mummolo 2018). Criminologists, psychologists, and sociologists have routinely argued that the police profession attracts people with certain personality traits, including "machismo, bravery, authoritarianism, cynicism, and aggression" (Twersky-Glasner 2005, 58).…”
mentioning
confidence: 99%
“…Research exploring the effect on Black women in particular have shown detrimental health and social consequences, from both direct and vicarious violent police contacts (Hitchens et al, 2018; Ritchie, 2017; Sewell & Jefferson, 2016). In addition, these interactions might exacerbate already fractured relationships between communities of color and law enforcement, further reducing trust and police legitimacy, and compromising crime control, especially in communities with high crime rates (Gaston et al, 2019; Haider-Markel & Joslyn, 2017; Jackson et al, 2013; Lum & Nagin, 2017; Skogan & Frydl, 2004; Skolnick, 1999).…”
Section: Introductionmentioning
confidence: 99%